Bio-based phytic acid and tannic acid chelate-mediated interfacial assembly of Mg(OH)2 for simultaneously improved flame retardancy, smoke suppression and mechanical properties of PVC. (1st May 2020) - Meng, Weihua; Dong, Yanli; Li, Jiahe; Cheng, Luyao; Zhang, Hongjie; Wang, Chunzheng; Jiao, Yunhong; Xu, Jianzhong; Hao, Jianwei; Qu, Hongqiang
Abstract: A bio-based Mg(OH)2 @tin phytate@zinc tannate (MH@PASn@TAZn) composite was synthesised via layer-by-layer assembly method. Chemical bonds formed by chelating metal ions with phytic acid and tannic acid were involved in this synthesis. MH@PASn@TAZn was then incorporated into PVC and its effects on flame retardancy, smoke suppression and mechanical properties were investigated. The core-shell structure and binding states between each layer (Mg–O–P, P–O–C) of the composite were examined. The limiting oxygen index (LOI) and cone calorimeter test results showed that the addition of 10 ph MH@PASn@TAZn effectively enhanced the flame retardancy and smoke suppression of PVC. The LOI value of the 10 ph MH@PASn@TAZn-incorporated PVC sample increased to 30.3% because of the combination of the gas dilution effect of vapor generated by the degradation of MH and synergistic catalytic carbonisation of PASn and TAZn. The second peak heat release rate, second peak smoke production rate and total smoke production of PVC/MH@PASn@TAZn composite decreased by 40.8%, 72.2% and 35.2%, respectively. The increase in the interfacial contact area of PASn and the enhancement of interfacial interaction of TAZn significantly improved the tensile strength, elongation at break, and impact strength of PVC. This study presents a promising approach to synthesise flame-retardant PVC with excellent smoke suppression and mechanical properties. Graphical abstract: Image 1 Highlights: A novel bio-based MH@PASn@TAZn was designed via layer-by-layer assembling technique and incorporated into flexible PVC. The core-shell structure and binding states between each layer (Mg–O–P, P–O–C) was characterized and confirmed. The flame retardancy and smoke suppression of the composites were improved dramatically by the synergistic action. The mechanical property was significantly improved with assistance of assembly layer.